(untitled) (Jurnal Mu’allim, 2026)
This study aims to initiate a conceptual framework of wiqayah tarbawiyah based on QS at-Tahrim 6 for Islamic family education in the digital era. While existing studies on QS at-Tahrim 6 focus on family resilience or parental authority, none have formulated an integrated preventive framework derived explicitly from the concept of wiqayah. This research employs a qualitative approach with a library research design, conducting a thematic analysis of Qur’anic exegesis on the command "qū," exploring the wiqayah concept, and critically reviewing twenty-two academic sources (2014–2025) on digital-era Muslim parenting. The exegetical analysis reveals a consensus among mufassirs interpreting the command "qū" not as a passive prohibition, but as an active and proactive protective mandate against Hellfire . By synthesizing these exegetical findings with contemporary studies, this research formulates a conceptual framework of wiqayah tarbawiyah grounded in three integrated pillars: the strengthening of creed, the habituation of worship, and the cultivation of morals. This framework serves as a multi-layered defense mechanism to protect families from digital moral disruptions, offering a novel theoretical foundation for preventive-oriented Islamic family education studies. Abstrak Penelitian ini bertujuan menginisiasi kerangka konseptual wiqayah tarbawiyah berbasis QS at-Tahrim 6 untuk pendidikan keluarga Islam di era digital. Meskipun studi terdahulu tentang QS at-Tahrim 6 telah banyak membahas ketahanan keluarga atau otoritas pengasuhan, belum ada yang merumuskan kerangka preventif terintegrasi yang diturunkan secara eksplisit dari konsep wiqayah. Penelitian ini menggunakan pendekatan kualitatif dengan desain studi kepustakaan melalui analisis tematik tafsir QS at-Tahrim 6, eksplorasi konsep wiqayah, serta analisis kritis terhadap dua puluh dua literatur (2014–2025) mengenai pengasuhan Muslim digital. Hasil analisis tafsir menunjukkan adanya konsensus para mufassir yang memaknai perintah “qū” bukan sekadar larangan pasif, melainkan sebuah komando penjagaan aktif dan proaktif . Melalui sintesis temuan tafsir dan kajian kontemporer, penelitian ini memformulasikan kerangka konseptual wiqayah tarbawiyah yang bertumpu pada tiga pilar terintegrasi: penguatan akidah, pembiasaan ibadah, dan pembinaan akhlak. Ketiga pilar ini berfungsi sebagai sistem perlindungan berlapis bagi orang tua dan anak dari risiko disrupsi moral digital, sekaligus menawarkan landasan teoretis baru bagi studi pendidikan keluarga Islam yang berorientasi pada fungsi preventif.